Potato Vine Killing or Desiccation - Chad M. Hutchinson; William M. Stall (EDIS, 2003)
Proper tuber maturity at harvest is an important factor in producing high quality Florida fresh market potatoes. A mature tuber has improved skin-set, bruise resistance, and storage life. Vine killing not only benefits tuber appearance but can also limit tuber size and improve tuber release from the vine at harvest. Tubers naturally mature as the potato plant senesces. However, improved production methods cause potato vines to remain healthy and green longer into the season. Tuber maturation can be artificially induced by killing the potato vines. The three traditional methods for vine killing are mechanical, chemical, and combinations of the mechanical and chemical methods. This document is HS925, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June 2003.